Core circadian clock transcription factor BMAL1 regulates mammary epithelial cell growth, differentiation, and milk component synthesis. - Theresa Casey (Public Library of Science (PLoS), 2021)
The role the mammary epithelial circadian clock plays in gland development and lactation is unknown. We hypothesized that mammary epithelial clocks function to regulate mammogenesis and lactogenesis, and propose the core clock transcription factor BMAL1:CLOCK regulates genes that control mammary epithelial development and milk synthesis. Our objective was to identify transcriptional targets of BMAL1 in undifferentiated (UNDIFF) and lactogen differentiated (DIFF) mammary epithelial cells (HC11) using ChIP-seq. Ensembl gene IDs with the nearest transcriptional start site to ChIP-seq peaks were explored as potential targets, and represented 846 protein coding genes common to UNDIFF and DIFF cells and 2773 unique to DIFF samples. Genes with overlapping peaks between samples (1343) enriched cell-cell adhesion, membrane transporters and lipid metabolism categories. To functionally verify targets, an HC11 line with Bmal1 gene knocked out (BMAL1-KO) using CRISPR-CAS was created. BMAL1-KO cultures had lower cell densities over an eight-day growth curve, which was associated with increased (p<0.05) levels of reactive oxygen species and lower expression of superoxide dismutase 3 (Sod3). RT-qPCR analysis also found lower expression of the putative targets, prolactin receptor (Prlr), Ppara, and beta-casein (Csn2). Findings support our hypothesis and highlight potential importance of clock in mammary development and substrate transport.